2007
DOI: 10.1074/jbc.m608619200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Aquifex aeolicus Argonaute Highlights Conformational Flexibility of the PAZ Domain as a Potential Regulator of RNA-induced Silencing Complex Function

Abstract: Gene silencing mediated by RNA interference requires the sequence-specific recognition of target mRNA by the endonuclease Argonaute, the primary enzymatic component of the RNA-induced silencing complex. We report the crystal structure of Aquifex aeolicus Argonaute, refined at 3.2 Å resolution. Relative to recent Argonaute structures, a 24°reorientation of the PAZ domain in our structure opens a basic cleft between the N-terminal and PAZ domains, exposing the guide strand binding pocket of PAZ. This rearrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…2 and 3 showed that G was preferred over C at most middle positions in vsiRNA asymmetry. This seems to support a hypothesis that flexibility of the RNA binding PAZ domain may contribute to recognition of siRNA in "initial loading" to the AGO complex (Rashid et al, 2007) and further suggests that the PAZ domain of plant AGO may operate a generic preference of G over C. Alternatively, the PIWI domain (Ma et al, 2005;Parker et al, 2005) may mediate unknown catalytic bias that leads to survival of the G-rich strand. Fig.…”
Section: Discussionsupporting
confidence: 64%
“…2 and 3 showed that G was preferred over C at most middle positions in vsiRNA asymmetry. This seems to support a hypothesis that flexibility of the RNA binding PAZ domain may contribute to recognition of siRNA in "initial loading" to the AGO complex (Rashid et al, 2007) and further suggests that the PAZ domain of plant AGO may operate a generic preference of G over C. Alternatively, the PIWI domain (Ma et al, 2005;Parker et al, 2005) may mediate unknown catalytic bias that leads to survival of the G-rich strand. Fig.…”
Section: Discussionsupporting
confidence: 64%
“…S10). 11,33 We were able to follow ternary complex formation in gel shift experiments, which showed that MjAgo efficiently binds DNA/DNA and DNA/RNA hybrids. Target strand incorporation was not observed if a DNA/DNA hybrid was used that carried a tandem mismatch as common in miRNAs that are recognized by human Ago2.…”
Section: Discussionmentioning
confidence: 98%
“…The first Ago structure published was that of an archaeal homolog isolated from Pyrococcus furiosus. 8 Since then, structures of Ago derived from bacterial, 11,12 archaeal, 8,13 and recently from eukaryotic sources [14][15][16] have been solved and show a high degree of similarity. 17,18 The protein is composed of an N-terminal domain, a PAZ, middle (MID), and PIWI domain (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these divergent modes of action, bacterial and archaeal Argonaute proteins adopt a highly conserved bilobed architecture. Herein, an N-terminal and a PIWI-ArgonauteZwille (PAZ) domain constitute one lobe, whereas the other lobe consists of the middle (MID) domain and the catalytic RNase H-like P element-induced wimpy testis (PIWI) domain (9)(10)(11)(12)(13)(14)(15). Molecular structures of a eukaryotic Argonaute MID domain and an Archaeoglobus fulgidus Piwi (AfPiwi) enzyme bound to a guide RNA showed the importance of the 5′-terminal base identity, as well as the 5′ phosphate in guide strand binding, to Ago (10,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%